Content analysis method: A tool to un-hide gender inequalities in the images of English coursebooks made in Argentina - Martín Cieri (Perspectivas Metodológicas​)
The content analysis method is an essential tool to identify the various ideological positions of publishing houses as regards the manifest and latent content in their textbooks. In this paper, this method is described and used in order to inquire about the links between the hidden curriculum as a gender device (Da Silva, 1995, 2001a, 2001b) and the reproduction and/or possible transformations, total or partial, of the roles historically assigned to gender based on the “biological” sex in the images in primary level English coursebooks made in Argentina. The results show that, despite the legal progress in gender and sexuality made between 2006 and 2012, the occupations of women presented in the images do not tend to multiply and diversify, nor do they accompany the professionalization of women. The images still show women in traditional and predominant roles, this reflecting a social reality that would persist almost immutable. However, certain categories analyzed reflect a greater equality between men and women; others show relative equality; while others suggest inequality in its omission.